Implementasi Artificial Intelligence pada Mahasiswa dalam Proses Pembelajaran Berdiferensiasi - Assidik, Gallant Karunia; Lesty, Merby Ariana (UM Purwokerto Press, 2024)
This study aims to determine the implementation of artificial intelligence (AI) integrated in the differentiated learning process in students. AI leads to more effective, active learning, and students are able to improve their thinking power. The research approach used is quantitative research with experimental methods. The research design used is quasi experimental design using one group pre-test and post-test design. Data were collected using meta-skills instrument in the form of questionnaire and analyzed using statistical paired sample t-test. The results showed that the implementation of AI has a positive impact on differentiated learning, as evidenced by the percentage of 85% of students strongly agree that the use of AI helps them in writing a standard language and provides convenience in essay writing courses, while 15% of other students disagree, because the use of AI is still relatively new for them. AI provides various platforms that are beneficial for students, including Grammarly, Quillbot, ChatGPT, Writelab, Smartick, and others.